A floor panel for an aircraft, and an aircraft comprising such a floor panel - NEHRING, ECKHARD (2016)
Described and illustrated is a floor panel (1) for an aircraft, said floor panel (1) comprising a panel structure (3) for transmitting forces applied to the floor panel (1), wherein the panel structure (3) includes an upper cover layer (7), a lower cover layer (9), and a core assembly (11) sandwiched between the upper and lower cover layers (7, 9), and a heater layer (5) for heating the floor panel (1), wherein the heater layer (5) is provided between the upper and lower cover layers (7, 9). The object of the present invention, to provide a possibly simple heated floor panel for an aircraft, wherein the risk of overheating and at the same time the risk of local hot spots at the heater layer is reduced, is achieved in that the heater layer (5) is formed as a PTC-layer having a plurality of electric conductor paths (27) interconnected to one another by a plurality of PTC-resistor paths (29) comprising a PTC-material, wherein the electric resistance of said PTC-Material increases with increasing temperature.